The Influence of a Tentative Diagnosis on the Identification of Features from Patient Appearance - Leblanc, Vicki R. (My University, 2000)
The clinical signs that a physician can identify from the appearance of a patient represent an important source of information, upon which the diagnostic decision is nominally based. Most of the research in medical education emphasizes the organization of medical knowledge or the reasoning processes based on these signs. This emphasis carries the implicit assumptions that identifying features is not the major problem and that evaluation of the clinical signs occurs largely independently of consideration of the diagnosis. However, there is accumulating evidence to suggest that the identification of these clinical signs can be influenced by the diagnosis being evaluated. The studies in this thesis contribute to this body of research by investigating the underlying processes by which the diagnosis being considered influences feature identification. Participants in these experiments were asked to identify the clinical signs from photographs of patients or electrocardiogram strips after having been biased towards the correct or an alternate diagnosis. It was found that the availability of a diagnosis served both to change the probability of reporting relevant clinical signs as well as to influence the identification of ambiguous signs. Manipulating the credibility of the suggested diagnosis, subsequently suggesting a second diagnosis, or decreasing the size of the pool of alternatives available to the diagnostician had a large impact on diagnostic conclusions, but produced relatively small effects on the features reported. These results suggest that changing the degree of focus that a clinician places on the suggested diagnosis has a small effect on the identification of the features by comparison to the substantial effect of merely suggesting a diagnosis. Furthermore, it was found that the subsequent suggestion of a competing diagnosis did not lead to a reinterpretation of the data. This indicates that once clinicians have seen the evidence one way, they are unlikely to see and label it differently. The implication of these findings for research on medical decision making, the mental organization of medical categories, as well as medical education are discussed.
Identification of Features from Patient Appearance
Keywords: tentative diagnosis; patient appearance; identification features